Political Relations between Russia and Qacar Iran on the Eve of the Second Russian-Iranian war (1825-1826) - N. R. Gozalova (Научный диалог)
The background of the second Russian-Iranian war of 1825-1826 is considered. It is shown that for almost three decades from the beginning of the 19th century, Kajar Iran stubbornly and persistently fought with Russia for supremacy in the South Caucasus, while the first Russan-Iranian war of 1804-1813 ended with the defeat of Iran and the conclusion of the Gulistan Treaty. It is noted that, despite the peace treaty, tensions between the two countries persisted, since both states were dissatisfied with its conditions. The purpose of this article is to consider the prerequisites and reasons for the start of the second Russan-Iranian war and to answer a number of questions, in particular, whether the unratified Tiflis Treaty (1825) on border delimitation can be considered final; whether Great Britain was the culprit or instigator of the second Russan-Iranian war, as claimed in almost all Soviet and Russian historiography; why Britain did not provide the promised assistance to Qacar Iran under the Tehran Treaty of 1814. The author comes to the conclusion that in the second Russian-Iranian war, the policy of Kajar Iran was defensive in relation to Russia and was due to the expansionist actions of Russia in the region.